The world economy and financial system: A paradigm change offering a sustainable approach - Sumer, Levent (Switzerland Palgrave macmillan, 2023)
This book introduces a new economic and financial system to replace the flawed current system. The past financial crises, including the Great Depression, the Global Financial Crisis, the COVID-19 pandemic, and the ongoing war between Russia and Ukraine, have showed us that the global financial system has problems and that a paradigm change and mindset shift to provide a better world to society is essential.